Project Based Blended Learning Using Cognitive Conflict Strategy: A Framework for Effective Blended Learning - Dian Ratna Puspananda; Boedy Irhadtanto (Jurnal Pendidikan Edutama, 2023)
Abstract: Project-based learning is an alternative to train students' 21st century skills. In development of the digital, project-based learning can be implemented in a blended manner using a learning management system. However, learning using the LMS which is carried out independently by students is feared that students will experience cognitive conflict resulting in unadapted responses that will affect learning outcomes. Therefore, this study aims to develop a framework for project based blended learning using a cognitive conflict strategy. After reviewing the relevant theory and empirical findings, the research results provide a basic framework for the design of PjB2L using CCS.Abstrak: Pembelajran berbasis proyek menjadi salah satu alternatif untuk melatih ketrampilan abad 21 mahasiswa. Dengan perkembangan dunia digital pembelajaran berbasis proyek bisa diimplementasikan dengan secara blended dengan menggunakan learning management system. Namun pembelajaran menggunakan LMS yang dilakukan secara mandiri oleh mahasiswa dikhawatirkan mahasiswa mengalami konflik kognitf sehingga terjadi unadapted respon yang akan mempengaruhi hasil belajar. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan kerangka kerja mengenai project based blended learning menggunakan cognitive conflict strategy. Setelah meninjau teori yang relevan dan temuan empiris, hasil penelitian memberikan kerangka dasar untuk desain PjB2L using CCS.